Three-Dimensional Genomics: A New Perspective and Therapeutic Strategies in Prostate Cancer Research - Sun, Yixiang (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Prostate cancer (PC) poses significant health risks to men globally. Enhancing our understanding of prostate cancer biology is crucial for facilitating early diagnosis and effective treatment strategies. A multitude of high-throughput sequencing studies, encompassing whole genome resequencing, transcriptome sequencing, and genome-wide association studies, have unearthed vital point mutations, structural variations, and epigenomic alterations linked to prostate cancer. These findings have significantly enriched our knowledge of the genomic framework for prostate cancer. Still, these investigations have predominantly centered on the one- or two-dimensional landscape of the genome. Research in three-dimensional genomics underscores the critical role of the genome’s three-dimensional spatial structure in maintaining normal cellular functions. Additionally, it demonstrates that dysregulation of key genes in numerous cancers relates to the chromatin’s spatial organization across various levels. This article explores the intricate three-dimensional architecture of chromosomes. It outlines the progressive development of techniques used in three-dimensional genomic research and synthesizes the application of these techniques in the study of prostate cancer biology. Furthermore, it proposes potential therapeutic strategies for prostate cancer.